The fish helminth fauna of Lake Sevan during a period of water level change - R. L. Hovhannisyan; M. Ya. Rukhkyan; L. D. Harutyunova; M. Z. Magomedova; P. D. Magomedova (Юг России: экология, развитие, 2023)
Aim. The aim of the work is to study the fish helminth fauna of Lake Sevan basin.Material and Methods. Fish helminths and molluscs were collected from the Lake Sevan basin. A total of 214 specimens of fish were studied. The collection, cameral processing and determination of the material was carried out according to generally accepted methods. Statistical processing of the material was carried out using the BioStat 2009 computer program. 124 specimens of molluscs were examined from the littoral of the Lake Sevan. The collection and identification of molluscs was carried out according to generally accepted methods. The work was carried out at the Scientific Centre of Zoology and Hydroecology of NAS of the Republic of Armenia. Its own collections have been used as material.Results. Trematodes, cestodes, nematodes and acanthocephals were found аs a result of studies of fish from the Lake Sevan basin. The total infestation of the fish by helminths was 27.1 %. Six species of helminths have been identified, two of which are the first to be recorded in new hosts in Armenia. The higher infestations of fish were noted by metacercariae of the trematode Diplostomum sp. and plerocercoids of the cestode Ligula intestinalis. A brief analysis of the infestation of fish by the detected helminths is given.Conclusion. The species composition of the helminth fauna of fish in the Lake Sevan basin was studied. Pathogens of dangerous helminthiases causing the death of fish have been noted. Studies of the helminth fauna of fish in the Lake Sevan basin are relevant and will be continued. Most of the species of fish affected by helminths are of economic importance. Some species of the helminths which were found are very invasive and cause great damage to the fisheries of the republic.